ANALISA TIMER ALAT SHORTHWAVE DIATHERMY MEREK BTL 6000 - Istiadi Ramadhan; Siti Rahmah (JURNAL MUTIARA ELEKTROMEDIK, 2018)
Shortwave Diathermy BTL 6000 is a therapy device that emits short waves that are used to warm up deep tissues and blood vessels. Shortwave Diathermy utilizes a certain frequency as a heat generator which is channeled into the patient's body tissues through electrodes and how does the time of therapy affect the heat of the body being treated. Research on Timer Analysis of the BTL 6000 Brand Shortwave Diathermy Tool was carried out using 3 time trials, then the timing was compared to the measuring instrument used, namely a stopwatch. The time settings used include 10 minutes, 20 minutes and 30 minutes. The BTL 6000 Brand Shortwave Diathermy Tool worked well, the device's Timer setting system worked well, and the stopwatch was used as a comparison tool for timer measurements. Timer setting with a time of 10 Minutes, there is a time difference of 12 seconds faster than the stopwatch, Frequency mode with output power of 50 Watt, frequency 300 Hz and Effect Power 6.0 Watt. , Continuous Mode with 20 Watt output power, and 20 Watt Effect Power, While on the timer setting with a time of 30 minutes, there is a difference in time of 9 seconds longer than the stopwatch, Continuous Mode with 20 Watt power output, and Effect Power 20 Watt, In this mode Continuous, the output of the tool has the same output, with output power = 20 Watts, medium effect Power = 20 Watts too